Canada - Theo, L. (Toronto : The Fideler Company, 1967)
Introduces our northern neighbor, its history, geography, government, economy, plants and animals, people, and culture.
Includes bibliographical references and index.
Keywords: Canada; Canada -- Juvenile literature